The effectiveness of gentle prenatal yoga on the recovery of depression level in pregnant women aged - Kiki Reski Rahmadani Bakri; Andi Nilawati Usman; Saidah Syamsuddin; Irfan Idris; Erlyn Limoa (Elsevier, 2021)
Objective: This study aimed to analyze the effectiveness of gentle prenatal yoga toward depression and abnormal serotonin hormone levels in pregnant women aged <20 and >35 years old. Method: This study was conducted at Bara Baraya Health Center, Antang Health Center, Kapasa Health Center, and Mamajang Health Center. The applied research design in this study was a quasi-experiment with a non-equivalent control group design approach. Samples were selected using a purposive sample technique. The instrument used was the Beck Depression Inventory (BDI) questionnaire. The number of samples in this study was 24 respondents divided into 2, 12 in the intervention group and 12 in the control group. Sample criteria in this study were pregnant women aged <20 and >35 years old, having been in trimester II-III with the gestational age of ≥20 to <31 weeks, and not having complications in pregnancy. Results: The mean values for the intervention group were 6.50 in the pre-test to the mid-test and 6.50 in the mid-test to the post-test. Meanwhile, the mean values for the control group were 5.61 in the pre-test to the mid-test and 4.50 in the mid-test to the post-test. This indicated that the intervention group experienced a significantly reduced level of depression based on the BD-II (Beck Depression Inventory-II) scores when compared to the control group. Furthermore, based on the comparison of the post-test data between the intervention group and the control group, it was obtained the p-value of 0.005 (α < 0.05). Conclusion: There were differences in BDI-II (Beck Depression Inventory-II) scores between the intervention group and the control group after receiving prenatal gentle yoga treatment.